Effective Method of Lecturing - Abdullaeva Umida Nigmatullayevna; Abdullayeva Shohistaxon Sharof qizi; Mamatisayeva Mubina Shuxrat qizi (Euro Asian Journal Publishing, 2024)
Perusing is an movement with a reason . A individual may studied in arrange to pick up data or confirm existing information , or in arrange to evaluate a writer s thoughts or composing fashion . A individual may moreover perused for satisfaction , or to upgrade information of the dialect being studied . The reason for perusing too decides the fitting approach to perusing comprehension
Keywords: Individual; teaching; reading; speaking